Dlaczego potrzebujemy e-administracji? Rozwój podstawowych umiejętności cyfrowych pracowników administracji na Pomorzu Zachodnim - Ewa Włodyka (Acta Politica Polonica, 2021)
The coronavirus pandemic of 2020 has shown that existing socio-economic and political patterns will not work in the new reality. It affects both the public and private sectors. In an era of constraints caused by a pandemic, it is essential to ensure that public administrations respond quickly and adequately to citizens’ needs. In addition, employers are looking for employees who have basic digital competences in addition to specific professional qualifications. Can e-government, understood as the process of using modern information and communication technologies in the functioning of public administration, be an answer to these problems? In this article I propose a thesis that the pandemic-forced development of e-government implies having basic digital competences, which public institutions and private sector companies with administrative employees in Central Pomerania as employers will require from their employees now and in the future.